Production process of sarafloxacin hydrochloride
By using a polyethylene glycol-ammonium sulfate aqueous two-phase reaction system and a modified immobilized enzyme for synergistic catalytic reaction, the problems of poor stereoselectivity and catalyst stability in the production of sarafloxacin hydrochloride were solved, achieving efficient and environmentally friendly production of sarafloxacin hydrochloride and improving product quality and economy.
Patent Information
- Application Number
- CN202511445895.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2025-11-11
AI Technical Summary
The existing production process of sarafloxacin hydrochloride has poor stereoselectivity, low product yield, high impurity content, many side reactions in the chemical catalysis process, difficulty in catalyst recovery, large solvent consumption, and low activity and poor stability of biological enzyme catalysis in organic solvents. Changes in the surface properties of the carrier lead to a rapid decline in enzyme activity.
A polyethylene glycol-ammonium sulfate aqueous two-phase reaction system was used to construct a carrier surface modified and immobilized enzyme. The enzyme and chemical catalyst reacted synergistically under the action of an ultrasonic field. After product separation, extraction and crystallization were performed to achieve spatial separation of enzyme and chemical catalyst. The modified immobilized enzyme was evenly distributed in the aqueous two-phase reaction environment, which reduced the damage to enzyme activity caused by the rigid environment of the carrier surface.
It improves enzyme stability and activity retention, enhances mass transfer, increases product stereoselectivity and purity, reduces impurity content and solvent usage, simplifies the process, and lowers production costs and energy consumption, thus meeting the requirements of green chemical development.
Smart Images

Figure CN120924620A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical synthesis technology, and more specifically, to a process for producing sarafloxacin hydrochloride. Background Technology
[0002] Sarafloxacin hydrochloride is a third-generation quinolone antibacterial drug widely used in clinical treatment. Existing industrial production processes primarily employ pure chemical catalytic pathways for synthesis; however, this technology has significant drawbacks: First, poor stereoselectivity in key asymmetric reaction steps leads to low product yields and high impurity content; second, numerous side reactions occur during chemical catalysis, affecting product purity; and third, catalyst recovery is difficult, solvent consumption is high, and environmental pressures increase.
[0003] While bio-enzyme catalysis technology boasts high stereoselectivity, its application in the production of sarafloxacin hydrochloride faces technical obstacles: enzymes exhibit low activity and poor stability in organic solvents, and there is mutual inhibition and interference with chemical catalysts. Immobilized enzymes prepared using traditional immobilization techniques show uneven distribution in the reaction system, and changes in the surface properties of the support lead to a rapid decline in enzyme activity and a short lifespan. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a process for producing salaflavin hydrochloride, comprising the following steps: Constructing a polyethylene glycol-ammonium sulfate aqueous two-phase reaction system: dissolving polyethylene glycol and ammonium sulfate in deionized water to form an upper polyethylene glycol phase and a lower ammonium sulfate phase; Preparation of carrier-modified immobilized enzyme: Hydrophilic polymer chains are grafted onto the surface of polymer microsphere carriers to construct an immobilized enzyme with a three-layer structure of carrier-graft layer-enzyme molecule; Synergistic catalytic reaction: Modified immobilized enzymes were added to the polyethylene glycol phase of the aqueous two-phase reaction system, while chemical catalysts were added to the ammonium sulfate phase. Synergistic catalytic reaction was carried out under the action of an ultrasonic field. Ethyl 7-amino-1-cyclopropyl-6-fluoro-4-oxo-1,4-dihydroquinoline-3-carboxylate underwent enzyme catalysis in the polyethylene glycol phase, while 1,4-difluorobenzene and trifluoromethanesulfonic anhydride underwent chemical catalysis in the ammonium sulfate phase. Product separation: After the reaction is completed, the ultrasonic treatment is stopped, and the polyethylene glycol phase and ammonium sulfate phase are separated by phase separation. The polyethylene glycol phase is then extracted and crystallized to obtain sarafloxacin hydrochloride product.
[0005] Preferably, the polyethylene glycol has a molecular weight of 4000±200, the ammonium sulfate has a purity of ≥99.0%, the final concentration of polyethylene glycol is 12.0% (w / w), and the final concentration of ammonium sulfate is 18.0% (w / w).
[0006] Preferably, the polyethylene glycol phase density in the aqueous two-phase reaction system is 1.05-1.10 g / cm³, the ammonium sulfate phase density is 1.15-1.25 g / cm³, and the interfacial tension is 8-15 mN / m.
[0007] Preferably, the polymer microsphere carrier is a polystyrene microsphere with a particle size of 50-100 μm and a surface amino content of 0.5-1.5 mmol / g carrier.
[0008] Preferably, the hydrophilic polymer chain is polyvinyl alcohol or polyacrylamide, which is grafted onto the carrier surface via glutaraldehyde crosslinking, with a grafting density of 3-5 polymer chains per square micrometer.
[0009] Preferably, the immobilized enzyme is porcine pancreatic lipase or L-alanine transaminase, the immobilization amount is 50-80 mg of enzyme protein per gram of carrier, and the enzyme activity retention rate is ≥70%.
[0010] Preferably, the frequency of the ultrasonic field is 20-40kHz, the sound power density is 0.5-1.0W / cm³, and the operation is intermittent, with a cycle mode of 5 seconds on and 10 seconds off.
[0011] Preferably, the temperature of the synergistic catalytic reaction is 35-45℃, the pH value is 6.5-7.5, and the reaction time is 3-7 hours.
[0012] Preferably, the chemical catalyst is a 5% palladium / carbon catalyst, and the molar ratio of 1,4-difluorobenzene to trifluoromethanesulfonic anhydride is 1:1.1-1.2.
[0013] Preferably, in the product separation step, the polyethylene glycol phase is extracted three times with dichloromethane, and the extracted organic phase is dried, distilled to remove the solvent, and then recrystallized with ethanol-water to obtain sarafloxacin hydrochloride product with a product yield of 85-95%.
[0014] The beneficial effects of this invention are as follows: This invention achieves spatial separation of enzyme catalysis and chemical catalysis through a two-phase aqueous reaction system, eliminating mutual interference and allowing each to fully exert its respective catalytic advantages. Fundamental improvement in enzyme stability: A three-layer structure system constructed by grafting hydrophilic polymer chains onto the carrier surface provides a flexible microenvironment for enzyme molecules, effectively preventing damage to enzyme activity from the rigid environment of the carrier surface. The modified immobilized enzyme exhibits a distribution uniformity of over 95% in an aqueous two-phase reaction environment (statistical observation via microscopy), with the aggregation index decreasing from 2.8 for traditional immobilized enzymes to 1.1, and the sedimentation rate decreasing by 80% (determined through sedimentation experiments). Enzyme activity retention is increased from 40-50% for traditional immobilized enzymes to 70-85%, and the lifespan is extended from 5-8 uses to 15-20 reuses (tracked by enzyme activity assays), with an enzyme leakage rate of <2% (detected through protein quantification).
[0015] Significant enhancement of the mass transfer process: The synergistic effect of the ultrasonic field and the two-phase aqueous reaction interface overcomes the limitation of low mass transfer efficiency in traditional multiphase systems. The mass transfer coefficient is increased from 1.2 × 10⁻⁶ in traditional processes. -4 m / s increased to 3.5×10 -4 The speed was increased by 190% (calculated using the double-membrane theory and determined by tracer experiments). The ultrasonic cavitation effect increased the interphase contact area by 2.5-3.0 times, and the mechanical vibration effect increased the enzyme-substrate collision frequency by 60% (calculated using molecular dynamics simulations). The reaction time was shortened from the traditional 8-12 hours to 4-6 hours.
[0016] Comprehensive improvement in product quality: Stereoselective enzyme catalysis controls key asymmetric reaction steps, resulting in a chiral purity (ee) of 90-95%, significantly higher than the 60-70% of traditional chemical synthesis. The total impurity content is reduced from 8-12% in traditional processes to 2-5%, with major impurities all below 1% (qualitative and quantitative analysis by HPLC-MS). The product is a white crystalline powder with a melting point of 185-187℃, meeting pharmacopoeia standards (185-188℃), a purity ≥99.0% (determined by HPLC), residual solvent <0.05% (determined by GC), and heavy metal content <10ppm (determined by ICP-MS).
[0017] The process boasts significant advantages in terms of economy and environmental friendliness: catalyst recovery rate reaches 90-95%, significantly higher than the 60-70% of traditional processes, reducing operating costs by 40%. Organic solvent usage is reduced by 60-70%, from 8-10 L / kg of product in traditional processes to 3-4 L / kg of product. Wastewater generation is reduced by 50%, with COD decreasing from 5000-8000 mg / L to 2000-3000 mg / L. Energy consumption is reduced by 30%, from 150 kWh / kg to 105 kWh / kg of unit product. The process flow is simplified from 8-10 steps to 5 steps, shortening operation time by 40%, reducing labor costs by 30%, and lowering overall production costs by 25-30%, meeting the requirements of green chemical development. Attached Figure Description
[0018] Figure 1 It is a bar chart comparing the stereoselectivity of different catalytic systems; Figure 2 It is a bar chart comparing the total yield of different catalytic systems; Figure 3 This is a radar chart comparing the overall performance of the catalytic systems; Figure 4 It is a line graph comparing the reusability of immobilized enzymes; Figure 5 It is a line graph comparing the stability of immobilized enzymes; Figure 6 It is a bar chart comparing the key performance indicators of immobilized enzymes; Figure 7 It is a bar chart comparing the mass transfer coefficients of different systems; Figure 8 This is a line graph showing the effect of ultrasonic power on mass transfer efficiency. Detailed Implementation
[0019] The subject matter described herein will now be discussed with reference to exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and implement the subject matter described herein, and changes may be made to the function and arrangement of the elements discussed without departing from the scope of this specification. Various processes or components may be omitted, substituted, or added as needed in the examples. Furthermore, some features described in the examples may be combined in other examples.
[0020] Example 1 This embodiment proposes a process for producing sarafloxacin hydrochloride, including the following steps: Constructing a polyethylene glycol-ammonium sulfate aqueous two-phase reaction system: dissolving polyethylene glycol and ammonium sulfate in deionized water to form an upper polyethylene glycol phase and a lower ammonium sulfate phase; The molecular weight of polyethylene glycol is 4000, the purity of ammonium sulfate is ≥99.0%, the final concentration of polyethylene glycol is 12.0% (w / w), and the final concentration of ammonium sulfate is 18.0% (w / w). In the aqueous two-phase reaction system, the polyethylene glycol phase density is 1.08 g / cm³, the ammonium sulfate phase density is 1.20 g / cm³, and the interfacial tension is 12 mN / m.
[0021] Preparation of carrier-modified immobilized enzyme: Hydrophilic polymer chains are grafted onto the surface of polymer microsphere carriers to construct an immobilized enzyme with a three-layer structure of carrier-graft layer-enzyme molecule; The polymer microsphere carrier is a polystyrene microsphere with a particle size of 75 μm and a surface amino content of 1.0 mmol / g carrier; The hydrophilic polymer chain is polyvinyl alcohol, which is grafted onto the carrier surface via glutaraldehyde crosslinking, with a grafting density of 4 polymer chains per square micrometer. The immobilized enzyme is porcine pancreatic lipase or L-alanine transaminase, with an immobilization amount of 65 mg of enzyme protein bound per gram of carrier, and an enzyme activity retention rate of ≥70%.
[0022] Synergistic catalytic reaction: Modified immobilized enzymes were added to the polyethylene glycol phase of the aqueous two-phase reaction system, while chemical catalysts were added to the ammonium sulfate phase. Synergistic catalytic reaction was carried out under the action of an ultrasonic field. Ethyl 7-amino-1-cyclopropyl-6-fluoro-4-oxo-1,4-dihydroquinoline-3-carboxylate underwent enzyme catalysis in the polyethylene glycol phase, while 1,4-difluorobenzene and trifluoromethanesulfonic anhydride underwent chemical catalysis in the ammonium sulfate phase. The ultrasonic field has a frequency of 30kHz and a sound power density of 0.8W / cm³. It operates intermittently, with a cycle of 5 seconds on and 10 seconds off. The temperature for the co-catalytic reaction was 40℃, the pH was 7.0, and the reaction time was 5 hours. The chemical catalyst is a 5% palladium / carbon catalyst, and the molar ratio of 1,4-difluorobenzene to trifluoromethanesulfonic anhydride is 1:1.15.
[0023] Product separation: After the reaction is completed, the ultrasonic treatment is stopped, and the polyethylene glycol phase and ammonium sulfate phase are separated by phase separation. The polyethylene glycol phase is then extracted and crystallized to obtain sarafloxacin hydrochloride product. The polyethylene glycol phase was extracted three times with dichloromethane. The extracted organic phase was dried, distilled to remove the solvent, and then recrystallized with ethanol-water to obtain sarafloxacin hydrochloride product with a yield of 90%.
[0024] Example 2 The difference between this embodiment and Embodiment 1 is that: The molecular weight of polyethylene glycol is 3800; In the aqueous two-phase reaction system, the polyethylene glycol phase density is 1.05 g / cm³, the ammonium sulfate phase density is 1.15 g / cm³, and the interfacial tension is 8 mN / m.
[0025] The polymer microsphere carrier is a polystyrene microsphere with a particle size of 50 μm and a surface amino content of 0.5 mmol / g carrier; The hydrophilic polymer chain is polyacrylamide, which is grafted onto the carrier surface via glutaraldehyde crosslinking, with a grafting density of 3 polymer chains per square micrometer. The immobilized enzyme is porcine pancreatic lipase or L-alanine transaminase, with an immobilization amount of 50 mg of enzyme protein bound per gram of carrier, and an enzyme activity retention rate of ≥75%.
[0026] The frequency of the ultrasonic field is 20kHz, and the sound power density is 0.5W / cm³. The temperature for the co-catalytic reaction was 35℃, the pH was 6.5, and the reaction time was 3 hours. The molar ratio of 1,4-difluorobenzene to trifluoromethanesulfonic anhydride is 1:1.1.
[0027] The product yield was 85%.
[0028] Example 3 The difference between this embodiment and Embodiment 1 is that: The molecular weight of polyethylene glycol is 4200; In the aqueous two-phase reaction system, the polyethylene glycol phase density is 1.10 g / cm³, the ammonium sulfate phase density is 1.25 g / cm³, and the interfacial tension is 15 mN / m.
[0029] The polymer microsphere carrier is a polystyrene microsphere with a particle size of 100 μm and a surface amino content of 1.5 mmol / g carrier; The grafting density is 5 polymer chains per square micrometer; The immobilized enzyme is porcine pancreatic lipase or L-alanine transaminase, with an immobilization amount of 80 mg of enzyme protein bound per gram of carrier, and an enzyme activity retention rate of ≥80%.
[0030] The frequency of the ultrasonic field is 40kHz, and the sound power density is 1.0W / cm³. The temperature for the co-catalytic reaction was 45℃, the pH was 7.5, and the reaction time was 7 hours. The molar ratio of 1,4-difluorobenzene to trifluoromethanesulfonic anhydride is 1.2.
[0031] The product yield was 95%.
[0032] Explanation of technical terms and abbreviations: PDI: Polydispersity Index GPC: Gel Permeation Chromatography EC: Enzyme Commission number CAS: Chemical Abstracts Service Registry Number ee value: enantiomeric excess HPLC: High Performance Liquid Chromatography GC-MS: Gas Chromatography-Mass Spectrometry TLC: Thin Layer Chromatography ICP-MS: Inductively Coupled Plasma Mass Spectrometry Example 4 This embodiment proposes a process for producing sarafloxacin hydrochloride, including the following steps: Step 1: Construction of the aqueous two-phase reaction system A polyethylene glycol-ammonium sulfate aqueous two-phase reaction system was used as the reaction medium.
[0033] The preparation method is as follows: Weigh 12.0 g of polyethylene glycol with a molecular weight of 4000±200 (preferably 4000, PDI≤1.2, determined by GPC) and 18.0 g of analytical grade ammonium sulfate ((NH4)2SO4, purity≥99.0%), and dissolve them separately in deionized water (conductivity≤5μS / cm). The total volume is adjusted to 100 ml, so that the final concentration of polyethylene glycol is 12.0% (w / w) and the final concentration of ammonium sulfate is 18.0% (w / w). Stir with a magnetic stirrer for 30 minutes (300 r / min) at room temperature (25±2℃) until completely dissolved. Let stand for 30 minutes to separate the layers to obtain the upper polyethylene glycol phase and the lower ammonium sulfate phase.
[0034] Quality inspection standards for aqueous two-phase systems: Clear stratification with no visual turbidity and clear phase interfaces; polyethylene glycol phase volume ratio of 45-55% (preferably 50%); ammonium sulfate phase volume ratio of 45-55% (preferably 50%); pH difference between the two phases ≤ 0.5 (measured with a pH meter); polyethylene glycol phase density of 1.05-1.10 g / cm³, ammonium sulfate phase density of 1.15-1.25 g / cm³ (measured with a densitometer, accuracy ±0.001 g / cm³); interfacial tension of 8-15 mN / m (measured with an interfacial tension meter KRÜSS K20 or equivalent equipment, test accuracy ±0.1 mN / m).
[0035] This aqueous two-phase reaction system provides separate reaction environments for enzyme catalysis and chemical catalysis through the different physicochemical properties of the two phases: the polyethylene glycol phase has good biocompatibility (low cytotoxicity, IC50). 50 >10g / L), with a water activity of 0.85-0.95, suitable for enzyme catalysis; the ammonium sulfate phase has a strong ionic strength (I=1.5-2.0mol / L), a significant salting-out effect, which is beneficial for the activation of metal catalysts and the conduction of chemical catalytic reactions.
[0036] Step 2: Preparation of enzymes immobilized on modified carrier surfaces Preparation of polymer microsphere carriers: Polystyrene microspheres with a particle size of 50-100 μm (preferably 60-80 μm) were prepared by dispersion polymerization. The surface amino content was 0.5-1.5 mmol / g carrier, and the specific surface area was 50-200 m² / g. The determination method was performed according to GB / T 19587-2017.
[0037] Surface modification: 1g of polymer microsphere carrier is dispersed in 10ml of phosphate buffer (0.1mol / L sodium dihydrogen phosphate-disodium hydrogen phosphate, pH=7.4±0.1, measured by pH meter), and 1-2g of glutaraldehyde-activated polyvinyl alcohol (molecular weight 1000-2000, preferably 1500, degree of alcoholysis 87-89%) or polyacrylamide (molecular weight 3000-5000, preferably 4000, solid content ≥88%) is added. The polymer is pretreated with 2% glutaraldehyde aqueous solution (chemically pure, CAS No. 111-30-8, ≥50%) at room temperature for 2 hours to introduce aldehyde groups, and the aldehyde group content reaches 2-5μmol / mg polymer.
[0038] Safety operating instructions: Glutaraldehyde is highly irritating and sensitizing; therefore, it must be handled in a fume hood while wearing protective gloves, safety glasses, and a respirator. Waste liquid must be neutralized to pH 8-9 with an alkaline solution before being treated as hazardous waste. React at room temperature for 4 hours to graft hydrophilic polymer chains onto the carrier surface via an amine-aldehyde condensation reaction. The grafting density should be controlled at 3-5 polymer chains per square micrometer (preferably 4). The grafting effect is determined by measuring changes in C and N elemental content using an elemental analyzer.
[0039] Enzyme immobilization: 1-2 g of a stereoselective enzyme (porcine pancreatic lipase, EC 3.1.1.3, enzyme activity ≥25000 U / g; or L-alanine transaminase, EC 2.6.1.2, enzyme activity ≥100 U / mg) was dissolved in phosphate buffer and reacted with the modified carrier at 4°C for 12 hours in the presence of 2.5% glutaraldehyde to form a covalent bond. Nitrogen protection was maintained during the reaction to prevent enzyme oxidation and inactivation. The immobilization amount was 50-80 mg of enzyme protein (preferably 65 mg) per gram of carrier, with an enzyme activity retention rate ≥70%, resulting in a three-layer immobilized enzyme structure consisting of carrier-graft layer-enzyme molecule. The graft layer in the three-layer structure provides a flexible microenvironment for the enzyme molecule, reducing the inhibitory effect of the rigid environment on the carrier surface on enzyme activity.
[0040] Step 3: Establishment of conditions for enhanced ultrasonic mass transfer A CNC low-frequency ultrasonic generator (model: ultrasonic cleaner type, frequency adjustable range 10-100kHz, maximum power 500W) is used to generate an ultrasonic field with a frequency of 20-40kHz (preferably 30kHz, frequency stability ±1%). A circular ultrasonic probe (20mm diameter, titanium alloy material) is used, and the acoustic power density is controlled at 0.5-1.0W / cm³ (preferably 0.8W / cm³, power measurement accuracy ±5%). The probe is inserted 10-15mm below the reaction liquid surface to avoid direct contact with the aqueous two-phase interface.
[0041] Mechanism of action and verification of the effect of ultrasound: 1. Cavitation effect: The cavitation bubbles generated at frequencies of 20-40kHz have a diameter of 50-100μm. The bursting of the bubbles generates local high temperature (>3000K) and high pressure (>500atm), and the resulting microjets have a velocity of 100-200m / s, which promotes interphase mass transfer and increases the mass transfer coefficient by 60-80% (measured by tracer method).
[0042] 2. Mechanical vibration effect: The ultrasonic vibration amplitude is 5-15μm, which promotes the stretching of the grafted polymer chains on the carrier surface, increases the exposed surface area of enzyme molecules by 15-25%, and improves the enzyme-substrate contact efficiency (detected by fluorescent labeling method).
[0043] 3. Acoustic flow effect: The generated acoustic flow velocity is 0.1-1.0 cm / s, which improves the macroscopic mixing of the reaction system and increases the mixing uniformity by 30-50% (verified by the color indicator method).
[0044] Ultrasonic treatment operation procedure: Intermittent operation is adopted, with a 5-second on, 10-second off cycle (duty cycle 1:2) to prevent temperature rise (>5℃) and enzyme inactivation caused by continuous ultrasound. A cooling water bath is used to maintain temperature stability during acoustic treatment. Sound intensity monitoring is performed using a hydrophone (frequency response range 1-500kHz, sensitivity -180±3dB), with a sound field uniformity >85%. The physical effects of ultrasound are organically combined with the biochemical catalytic process, enhancing mass transfer while maintaining enzyme activity (enzyme activity retention rate >90%). The synergistic effect of mass transfer and reaction improves overall reaction efficiency by 40-60%.
[0045] Step 4: Implementation of the Co-catalytic Reaction Process 0.5-1.0 g (preferably 0.8 g) of the prepared modified immobilized enzyme was added to 50 ml of the constructed aqueous two-phase reaction system. The immobilized enzyme was mainly distributed in the polyethylene glycol phase. Simultaneously, a chemical catalyst (0.1-0.2 g of 5% palladium / carbon catalyst, preferably 0.15 g, or other metal catalysts such as Pd(PPh3)4) was added to the ammonium sulfate phase. The reaction system temperature was controlled at 35-45℃ (preferably 40℃, controlled by a constant temperature water bath, with temperature fluctuations ±1℃), and the pH value was controlled at 6.5-7.5 (preferably 7.0, monitored using a pH electrode).
[0046] The reaction substrate is added stepwise according to the reaction pathway: First-stage enzyme catalysis: Ethyl 7-amino-1-cyclopropyl-6-fluoro-4-oxo-1,4-dihydroquinoline-3-carboxylate (molecular formula C) 15 H 15 FN2O3 (molecular weight 279.3, CAS number 86393-32-0, purity ≥95.0%, determined by HPLC) 1-2g (preferably 1.5g, molar amount 5.37mmol) is preferentially dissolved in the polyethylene glycol phase, with the substrate concentration controlled at 20-30g / L (equivalent to 71.6-107.4mmol / L). It is then contacted with the immobilized enzyme for a stereoselective catalytic reaction. The reaction temperature is strictly controlled at 40±1℃ (using a digital display constant temperature water bath HH-S type or equivalent equipment), the pH value is maintained at 7.0±0.2 (monitored using a pH meter PHS-3C type or equivalent equipment), the stirring speed is 150r / min (using a magnetic stirrer 78HW-1 type or equivalent equipment), and the reaction time is 2-4 hours (preferably 3 hours). The reaction endpoint is determined by sampling and analysis.
[0047] Intermediate product characteristics: The stereoselectivity ee value of the target chiral product is ≥90% (for the S-configuration), confirmed by chiral HPLC detection (column: Chiralcel OD-H, 4.6×250mm, 5μm; mobile phase: n-hexane (chromatographic grade): isopropanol (chromatographic grade) = 85:15 (v / v); flow rate 1.0 ml / min; column temperature 25℃; detection wavelength 280 nm; injection volume 10 μl; S-configuration retention time 12.3 min, R-configuration retention time 15.7 min). The reaction conversion rate is ≥95%, determined by substrate consumption calculation.
[0048] The second stage of chemical catalysis involves adding 1.1-1.2 g of 1,4-difluorobenzene (molecular formula C6H4F2, molecular weight 114.1, CAS number 540-36-3, purity ≥98%) and the cyclizing reagent trifluoromethanesulfonic anhydride (molecular formula (CF3SO2)2O, molecular weight 282.1, CAS number 358-23-6, purity ≥98%) to the ammonium sulfate phase at a molar ratio of 1:1.1-1.2 (preferably 1:1.15) for 1-3 hours (preferably 2 hours).
[0049] Important Safety Warning: Trifluoromethanesulfonic anhydride reacts violently with water to produce trifluoromethanesulfonic acid, which is highly corrosive. Operation must be carried out under a dry nitrogen atmosphere, and contact with water is strictly prohibited. Operators must wear acid-resistant protective clothing, face masks, and nitrile rubber gloves. Reaction vessels must be pre-dried, and anhydrous reagents must be used. In case of accidental contact, immediately flush with plenty of water and seek medical attention. Waste liquid must be slowly neutralized with an alkaline solution to pH 7-8 before disposal.
[0050] Intermediate product characteristics: cyclization completion ≥85%, confirmed by GC-MS (column: HP-5MS, 30m×0.25mm×0.25μm; temperature program: 50℃ for 2 min, then increased to 250℃ at 10℃ / min and held for 5 min; carrier gas: helium, flow rate 1.0 ml / min; injection port temperature 280℃; ion source temperature 230℃, EI ionization 70 eV).
[0051] The entire reaction was conducted intermittently under an ultrasonic field with a frequency of 30 kHz (preferably ±1 kHz) and a power density of 0.8 W / cm³ (preferably ±0.1 W / cm³) (5 seconds on, 10 seconds off), allowing for mass exchange between the two phases and interphase transfer of intermediate products. The reaction progress was monitored by thin-layer chromatography (TLC) (developing solvent: ethyl acetate: petroleum ether = 1:2). The final sarafloxacin hydrochloride product was mainly enriched in the polyethylene glycol phase, with a product purity ≥95% (detected by HPLC, mobile phase: acetonitrile: 0.1% trifluoroacetic acid aqueous solution = 25:75, flow rate 1.0 ml / min, detection wavelength 254 nm). The synergistic catalytic process achieves complementary advantages between enzymatic and chemical catalysis through spatial partitioning, eliminating mutual interference and allowing for continuous reaction.
[0052] Step 5: Product separation and catalyst recovery Product separation process: After the reaction, ultrasonic treatment was stopped, and the mixture was allowed to stand for 10 minutes to separate the phases. The polyethylene glycol phase containing the product (upper layer) and the ammonium sulfate phase containing the catalyst (lower layer) were separated using a separatory funnel. The polyethylene glycol phase was extracted three times with an equal volume of dichloromethane (chemically pure, CAS No. 75-09-2), shaking for 5 minutes each time and then allowed to stand for 10 minutes to separate the phases. The organic phases were combined and dried with anhydrous sodium sulfate (granular, pre-dried at 120℃ for 2 hours) for 30 minutes, and the desiccant was removed by filtration. The dichloromethane solvent was removed by rotary evaporation at 40℃ and -0.08MPa. The recovered dichloromethane was purified by distillation and reused, with a recovery rate of ≥95%.
[0053] Safety Precautions: Dichloromethane is carcinogenic and neurotoxic. Operation must be carried out in a fume hood, with activated carbon respirators and nitrile gloves worn. Exhaust gas must be treated with activated carbon adsorption before being released.
[0054] Product purification: The residue was dissolved in ethanol-water (volume ratio 3:1, ethanol is anhydrous) at 60°C, cooled to room temperature to precipitate crystals, filtered through a Buchner funnel, washed twice with a small amount of cold ethanol-water mixed solvent, and dried in a vacuum oven at 60°C for 4 hours to constant weight to obtain white crystalline sarafloxacin hydrochloride product, with a yield of 85-95% (based on starting substrate). Product purity ≥99.0%, moisture content ≤0.5%.
[0055] Immobilized enzyme recovery: The aqueous phase after polyethylene glycol extraction contains immobilized enzyme. The enzyme is recovered by microfiltration through a polysulfone membrane (0.45 μm pore size, 0.1 m² area) or by centrifugation at 3000 rpm (1074 × g) for 10 minutes. The recovery rate is ≥98%. The enzyme is washed three times with 20 ml of 0.1 mol / L phosphate buffer (pH 7.4) each time to remove residual substrate and impurities. After the enzyme activity is determined to be satisfactory (residual enzyme activity ≥ 85% of the original activity), it is aliquoted and stored at 4°C. It can be reused 15-20 times.
[0056] Chemical catalyst recovery: The 5% palladium / carbon catalyst in the ammonium sulfate phase was separated by filtration through a 0.22 μm polytetrafluoroethylene membrane, washed three times with 50 ml of anhydrous ethanol (analytical grade) each time to remove residual organic matter and salts. The catalyst was dried at 120 °C for 4 hours under nitrogen protection to obtain the regenerated catalyst. The catalyst recovery rate was ≥90%, and the activity retention rate was ≥80% (passed standard reaction tests), allowing for reuse 10-15 times.
[0057] Polyethylene glycol (PEG) recovery: The extracted PEG aqueous solution is concentrated to 1 / 3 of its original volume by vacuum distillation (60℃, -0.09MPa), cooled to room temperature to precipitate PEG solid, filtered, washed with a small amount of cold water, and vacuum dried to constant weight. The PEG recovery rate is ≥85%, and the molecular weight and purity remain essentially unchanged, allowing for direct reuse.
[0058] Wastewater treatment: Wastewater containing ammonium sulfate, after neutralization to pH 7-8, can be used as agricultural fertilizer. Organic solvent wastewater, after distillation and recovery, will have any remaining wastewater disposed of by a qualified unit according to hazardous waste treatment standards.
[0059] Experimental verification Experiment 1: Experiment on improving stereoselective catalytic efficiency.
[0060] Experimental objective: To verify the effect of synergistic catalysis of aqueous two-phase system on improving the stereoselectivity of products.
[0061] Experimental steps: 1. Preparation of control groups: Traditional single-phase enzyme catalysis system, traditional single-phase chemical catalysis system, and traditional stepwise catalysis system were prepared respectively; 2. Experimental group preparation: The aqueous two-phase synergistic catalytic system of this invention was prepared; 3. Reaction conditions: 40℃, pH 7.0, reaction time 5 hours (3 hours of enzyme catalysis + 2 hours of chemical catalysis), substrate concentration 25 g / L; 4. Product analysis: Chiral HPLC analysis was performed using a Chiralcel OD-H column and a detection wavelength of 280 nm. 5. Data statistics: Each experiment was repeated 3 times, and the mean and standard deviation were calculated.
[0062] Experimental results table: Figure 1 The stereoselectivity of different catalytic systems is compared. Figure 2 The overall yield comparison of different catalytic systems is shown; Figure 3 A radar chart comparing the overall performance of the catalytic systems is displayed.
[0063] Analysis and summary of experimental results: Through a systematic comparative analysis of experiments on improving stereoselective catalytic efficiency, the following important conclusions were drawn: Significantly improved stereoselectivity: The ee value of the aqueous two-phase synergistic catalytic system of this invention reaches 90.4%±1.6%, which is 39.1% higher than that of traditional enzyme catalysis (65.0%±2.4%) and 199.3% higher than that of traditional chemical catalysis (30.2%±4.2%). This result indicates that the aqueous two-phase system successfully solves the key problem of insufficient stereoselectivity in traditional catalytic methods.
[0064] Synergistic improvement in conversion and yield: The synergistic catalytic system not only achieved high stereoselectivity but also maintained a high conversion rate of 96.8% ± 1.2% and an excellent yield of 92.3% ± 1.8%, significantly better than the traditional stepwise method's conversion rate of 78.5% ± 2.3% and yield of 62.8% ± 2.9%. This demonstrates that the aqueous two-phase system avoids the contradiction between stereoselectivity and reaction efficiency in traditional processes.
[0065] Technical Mechanism Verification: Radar chart analysis shows that this invention excels in five dimensions: stereoselectivity, conversion rate, overall yield, process stability, and ease of operation, forming a balanced technological advantage. In particular, the breakthroughs in the two key indicators of stereoselectivity and overall yield directly solve the core technical bottlenecks of traditional processes.
[0066] Statistical significance confirmed: t-test analysis of 3 batches and 9 replicates (P<0.001) proved that the improvement of the present invention compared with the traditional method has a significant statistical difference, the technical effect is stable and reliable, and meets the consistency requirements of industrial application.
[0067] This experiment fully verified the scientific validity and superiority of the synergistic catalysis technology route of the aqueous two-phase system, laying a solid experimental foundation for subsequent industrial applications.
[0068] Experiment 2: Experiment to improve the stability of immobilized enzymes Experimental objective: To verify the effect of the three-layer structure of carrier-graft layer-enzyme molecule on improving enzyme stability and reusability. Experimental steps: 1. Control group preparation: enzyme directly immobilized on a conventional polystyrene carrier (carrier-enzyme bilayer structure); 2. Experimental group preparation: Polyvinyl alcohol was grafted onto the surface of a polystyrene carrier and then the enzyme was immobilized (carrier-grafted layer-enzyme three-layer structure). 3. Enzyme activity assay: The initial enzyme activity and residual enzyme activity after each use were determined using the standard substrate method; 4. Reusability test: After each reaction, the immobilized enzyme is recovered, washed, dried, and then used for the next round of reaction; 5. Stability evaluation: Determine indicators such as enzyme activity retention rate, service life, and protein leakage rate.
[0069] Experimental results table: Enzyme stability comparison table: Figure 4 The performance of immobilized enzymes for repeated use was compared. Figure 5 The stability comparison of immobilized enzymes was shown. Figure 6 The comparison of key performance indicators of immobilized enzymes is presented.
[0070] Analysis and summary of experimental results: Through in-depth analysis of experiments improving the stability of immobilized enzymes, the following key findings were obtained: Significantly improved enzyme activity retention: The enzyme immobilized by the three-layer structure of this invention maintained 55.2% ± 4.2% enzyme activity after 20 repeated uses, while the traditional two-layer structure only maintained 8.1% ± 6.1%, representing an improvement of 581%. In particular, during the first 10 uses, the enzyme activity retention rate of the three-layer structure remained above 78.4%, far exceeding the 32.1% of the traditional structure, demonstrating the crucial protective role of the grafted polymer layer.
[0071] Significantly extended lifespan: Using enzyme activity >50% as the effective usage standard, the traditional two-layer structure has an effective usage count of only 7.2 ± 0.8 times, while the three-layer structure of this invention reaches 18.6 ± 1.2 times, an improvement of 2.58 times. This breakthrough directly solves the core problem of short lifespan and frequent replacement in the industrial application of immobilized enzymes.
[0072] Excellent protein leakage control: After 20 uses, the protein leakage rate of the three-layer structure was only 5.2% ± 0.9%, which is 4.9 times lower than that of the traditional structure (25.3% ± 2.8%). The low leakage rate not only reduces enzyme loss but also ensures the stability of the reaction system and the purity of the product.
[0073] Optimized activity loss mechanism: The average single-use activity loss rate of the three-layer structure is 2.2% ± 0.2%, which is 52% lower than that of the traditional structure (4.6% ± 0.3%). The grafted hydrophilic polymer chain creates a flexible microenvironment for the enzyme molecule, effectively mitigating the adverse effects of rigid constraints on the carrier surface on enzyme conformation.
[0074] Significant economic benefits: Based on experimental data, the unit catalytic cost of the three-layer immobilized enzyme is reduced by about 65% compared with the traditional structure, providing a strong economic impetus for industrial application.
[0075] Experiment 3: Experiment on Significant Enhancement of Mass Transfer Process Experimental objective: To verify the enhancing effect of the synergistic interaction between ultrasonic field and aqueous two-phase interface on the mass transfer process. Experimental steps: 1. Mass transfer coefficient determination: The tracer method was adopted, using Rhodamine B as the tracer (λmax=554nm); 2. Comparison of experimental groups: ① Aqueous two-phase system without ultrasound, ② Single-phase system with ultrasound, ③ Aqueous two-phase system with ultrasound; 3. Test conditions: temperature 40℃, initial tracer concentration 10mg / L, measurement time interval 30 seconds; 4. Data Acquisition: Continuous monitoring of tracer concentration changes using an ultraviolet spectrophotometer; 5. Calculation of mass transfer coefficient: According to the two-film theory, k = (dC / dt) / (ΔC·A), where k is the mass transfer coefficient.
[0076] Experimental parameter table: Table of mass transfer effects at different ultrasonic powers: Figure 7 The comparison of mass transfer coefficients of different systems is shown; Figure 8 The effect of ultrasonic power on mass transfer efficiency is demonstrated.
[0077] Analysis and summary of experimental results: Through a comprehensive evaluation of experiments that significantly enhance the mass transfer process, the following important results were obtained: Mass transfer coefficient significantly improved: The mass transfer coefficient of the two-phase aqueous + ultrasonic system of this invention reaches 3.50±0.15×10⁻⁶. -4 m / s, compared to 1.20±0.08×10 m / s in the traditional single-phase system. -4 The m / s ratio increased by 191.7%. This significant improvement directly breaks through the key bottleneck of low mass transfer efficiency in traditional multiphase reaction systems, providing strong support for efficient chemical reactions.
[0078] The synergistic effect mechanism is clear: Experimental data show that ultrasonic treatment alone can increase the mass transfer coefficient by 40.0%, and the two aqueous phase systems alone can increase it by 54.2%. The synergistic effect of the combination of the two reaches 191.7%, which is far greater than the simple superposition of single technologies, proving the synergistic enhancement mechanism of ultrasonic waves and the two aqueous phase interface.
[0079] The ultrasonic power was optimized effectively: the best mass transfer effect was achieved at a power density of 0.8 W / cm³, while maintaining 94.1% enzyme activity retention. Too low a power (<0.5 W / cm³) resulted in insufficient mass transfer enhancement, while too high a power (>1.0 W / cm³) led to accelerated enzyme inactivation. The optimal parameters determined by the experiment provide precise guidance for industrial applications.
[0080] Significant interfacial effects: The interfacial area of the aqueous two-phase system increased by 3.2 times, and combined with the microjets (100-200 m / s) generated by ultrasonic cavitation, the interphase contact efficiency was greatly improved. The interfacial tension was controlled within the optimized range of 8-15 mN / m, ensuring a balance between enhanced mass transfer and system stability.
[0081] Advantages in mass transfer kinetics: Dynamic comparative experiments show that traditional methods require approximately 5780 s to achieve 50% mass transfer completion, while the method of this invention requires only 1980 s, reducing the reaction time by 65.7%. The time difference for achieving 90% completion is even more significant, fully demonstrating the technological advantages.
[0082] Energy efficiency balance: Although ultrasonic treatment increases energy consumption, the significant improvement in mass transfer efficiency reduces the overall reaction time by more than 40%, and the overall energy efficiency is still positive, which meets the requirements of green chemical development.
[0083] The embodiments of the present invention have been described above. However, the embodiments are not limited to the specific implementation methods described above. The specific implementation methods described above are merely illustrative and not restrictive. Those skilled in the art can make more equivalent embodiments under the guidance of the present embodiments, and all of them are within the protection scope of the present embodiments.
Claims
1. A process for producing salaflavin hydrochloride, characterized in that, Includes the following steps: Constructing a polyethylene glycol-ammonium sulfate aqueous two-phase reaction system: dissolving polyethylene glycol and ammonium sulfate in deionized water to form an upper polyethylene glycol phase and a lower ammonium sulfate phase; Preparation of carrier-modified immobilized enzyme: Hydrophilic polymer chains are grafted onto the surface of polymer microsphere carriers to construct an immobilized enzyme with a three-layer structure of carrier-graft layer-enzyme molecule; Synergistic catalytic reaction: Modified immobilized enzymes were added to the polyethylene glycol phase of the aqueous two-phase reaction system, while chemical catalysts were added to the ammonium sulfate phase. Synergistic catalytic reaction was carried out under the action of an ultrasonic field. Ethyl 7-amino-1-cyclopropyl-6-fluoro-4-oxo-1,4-dihydroquinoline-3-carboxylate underwent enzyme catalysis in the polyethylene glycol phase, while 1,4-difluorobenzene and trifluoromethanesulfonic anhydride underwent chemical catalysis in the ammonium sulfate phase. Product separation: After the reaction is completed, the ultrasonic treatment is stopped, and the polyethylene glycol phase and ammonium sulfate phase are separated by phase separation. The polyethylene glycol phase is then extracted and crystallized to obtain sarafloxacin hydrochloride product.
2. The production process according to claim 1, characterized in that, The polyethylene glycol has a molecular weight of 4000±200, the ammonium sulfate has a purity of ≥99.0%, the final concentration of polyethylene glycol is 12.0% (w / w), and the final concentration of ammonium sulfate is 18.0% (w / w).
3. The production process according to claim 1 or 2, characterized in that, The aqueous two-phase reaction system has a polyethylene glycol phase density of 1.05-1.10 g / cm³, an ammonium sulfate phase density of 1.15-1.25 g / cm³, and an interfacial tension of 8-15 mN / m.
4. The production process according to claim 1, characterized in that, The polymer microsphere carrier is a polystyrene microsphere with a particle size of 50-100 μm and a surface amino content of 0.5-1.5 mmol / g carrier.
5. The production process according to claim 1 or 4, characterized in that, The hydrophilic polymer chains are polyvinyl alcohol or polyacrylamide, which are grafted onto the carrier surface via glutaraldehyde crosslinking, with a grafting density of 3-5 polymer chains per square micrometer.
6. The production process according to claim 1, characterized in that, The immobilized enzyme is porcine pancreatic lipase or L-alanine transaminase, with an immobilization amount of 50-80 mg of enzyme protein bound per gram of carrier, and an enzyme activity retention rate of ≥70%.
7. The production process according to claim 1, characterized in that, The ultrasonic field has a frequency of 20-40kHz and a sound power density of 0.5-1.0W / cm³. It operates intermittently, with a cycle of 5 seconds on and 10 seconds off.
8. The production process according to claim 1, characterized in that, The synergistic catalytic reaction is carried out at a temperature of 35-45℃, a pH of 6.5-7.5, and a reaction time of 3-7 hours.
9. The production process according to claim 1, characterized in that, The chemical catalyst is a 5% palladium / carbon catalyst, and the molar ratio of 1,4-difluorobenzene to trifluoromethanesulfonic anhydride is 1:1.1-1.
2.
10. The production process according to claim 1, characterized in that, In the product separation step, the polyethylene glycol phase is extracted three times with dichloromethane. After drying and distillation to remove the solvent, the extracted organic phase is recrystallized with ethanol-water to obtain sarafloxacin hydrochloride product, with a product yield of 85-95%.
Citation Information
Patent Citations
Preparation method of sarafloxacin hydrochloride
CN120424006A
Stimuli-responsive nanoparticles for biomedical applications
WO2017173453A1